2010
DOI: 10.1161/hypertensionaha.109.141531
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reversal of Left Ventricular Hypertrophy and Intracardiac Volume Overload in Patients With Resistant Hypertension and Hyperaldosteronism

Abstract: Abstract-We have shown previously that patients with resistant hypertension and hyperaldosteronism have increased brain natriuretic peptide suggestive of increased intravascular volume. In the present study, we tested the hypothesis that hyperaldosteronism contributes to cardiac volume overload. Thirty-seven resistant hypertensive patients with hyperaldosteronism (urinary aldosterone Ն12 g/24 hours and plasma renin activity Յ1.0 ng/mL per hour) and 71 patients with normal aldosterone status were studied. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 44 publications
4
97
2
7
Order By: Relevance
“…This interpretation seems to be supported by studies of the LV pressure-volume curves in rats after aldosterone infusion 38 and also by human studies showing an increase in brain natriuretic peptide (BNP) levels in patients with PA. 39 Increased LV volumes compared with essential hypertension were confirmed also in a smaller group of patients with PA examined by magnetic resonance imaging (MRI) as a potentially more accurate method than commonly used echocardiography. 40 The present study shows that both adrenalectomy and mineralocorticoid receptor blockers can reverse the enlargement of the LV cavity during long-term follow-up, probably through the reduction of plasma volume and LV preload. In spite of the significant and similar blood pressure drop in both groups, however, only surgery led to a successful reduction in the thickness of LV walls.…”
Section: Discussionsupporting
confidence: 56%
“…This interpretation seems to be supported by studies of the LV pressure-volume curves in rats after aldosterone infusion 38 and also by human studies showing an increase in brain natriuretic peptide (BNP) levels in patients with PA. 39 Increased LV volumes compared with essential hypertension were confirmed also in a smaller group of patients with PA examined by magnetic resonance imaging (MRI) as a potentially more accurate method than commonly used echocardiography. 40 The present study shows that both adrenalectomy and mineralocorticoid receptor blockers can reverse the enlargement of the LV cavity during long-term follow-up, probably through the reduction of plasma volume and LV preload. In spite of the significant and similar blood pressure drop in both groups, however, only surgery led to a successful reduction in the thickness of LV walls.…”
Section: Discussionsupporting
confidence: 56%
“…28 Many studies have shown that left ventricular mass decreases and that aortic pulse wave velocity and carotid intima-media thickness improve after adrenalectomy. [29][30][31][32][33][34][35] A prospective study compared cardiovascular events in 54 PA patients treated by adrenalectomy (unilateral disease) or with spironolactone (unilateral or bilateral disease) with 323 patients with essential hypertension. 36 The composite endpoint was myocardial infarction, stroke, any type of revascularization procedure, and sustained arrhythmia.…”
Section: Outcomes Of Adrenalectomy In Unilateral Pamentioning
confidence: 99%
“…Fluid retention in cardiomyocytes influenced by aldosterone, and intracardiac volume increase, accompanied by increased intramural stress -in-wall-stress -should also be taken into consideration [17,34].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%